DESENVOLVIMENTO DE PESSOAS PARA SUSTENTABILIDADE EMPRESARIAL: UMA ANÁLISE COMPARATIVA DAS AÇÕES PROMOVIDAS POR EMPRESAS BRASILEIRAS - Arruda, Luis Roberto (2011)
This research comes from the observation that more and more Brazilian companies are implementing sustainable development strategies. However, each organization has its own opinions and approaches on how to deal with the challenges of sustainability. For this reason, the objective of this research is to analyze practices of staff development that contribute to better employee involvement with business sustainability, and to compare these practices with declared policies for sustainability. This is a qualitative research, based on exploratory stages and semi-structured interviews with Brazilian companies that publish sustainability reports. The results suggest four main conclusions: the polysemy of terms and concepts on Sustainable Development and Sustainability; the polarization of the debate on Sustainable Development and Sustainability in two opposing conceptual matrices; business investment in the preparation of employees to the Social Dialogue as a way of effectiveness of the policies of sustainability; and difficulties of companies to implement an Education for Sustainability because of the prevalence of corporate vision of education where the employee is more input, an operational man or reactive